2023
DOI: 10.1002/pc.27795
|View full text |Cite
|
Sign up to set email alerts
|

Fiberglass‐reinforced triply periodic minimal surfaces (TPMS) lattice structures for energy absorption applications

Shaun Ormiston,
Sriharsha Srinivas Sundarram

Abstract: Triply periodic minimal surfaces (TPMS)‐based lattice structures exhibit improved mechanical and energy absorption properties compared to other lattices. Fused filament fabrication is the preferred approach for fabricating these structures and majority of the existing TPMS structures are manufactured using a single polymer. This study presents composite lattice structures that are reinforced with a second material. TPMS lattice structures are designed using MSLattice and modeled into cubical, cylindrical, bar,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The structures were extruded from Nylon, which contains carbon fibers, and reinforced with glass fiber. The results showed, in this case, that the glass-fiber-reinforced structures with a reduction in the amount of material to a total of 25% had similar or better properties compared with structures with a 75% volume of the material without the addition of glass fiber reinforcement [14].…”
Section: State Of the Artmentioning
confidence: 78%
“…The structures were extruded from Nylon, which contains carbon fibers, and reinforced with glass fiber. The results showed, in this case, that the glass-fiber-reinforced structures with a reduction in the amount of material to a total of 25% had similar or better properties compared with structures with a 75% volume of the material without the addition of glass fiber reinforcement [14].…”
Section: State Of the Artmentioning
confidence: 78%
“…19 TPMSbased lattice structures have been found to exhibit improved mechanical and energy absorption properties compared to other lattices. 20 These lattice structures have been investigated for their effect on compression and tensile properties, fluid permeability, and thermal conductivity. Banerjee et al 21 demonstrated ultra-large elastic deformation of nanoscale diamond needles.…”
Section: Introductionmentioning
confidence: 99%